(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: Advaita Vedanta and Kashmir Shaivism represent two profound non-dualistic philosophies that challenge conventional perceptions of separation and multiplicity. This study examines their distinct interpretations of reality, exploring how each tradition articulates the unity of existence through differing metaphysical frameworks. Advaita Vedanta posits an absolute, formless Brahman as the singular reality, with individual selfhood viewed as an illusion arising from ignorance. In contrast, Kashmir Shaivism embraces a dynamic, creative process where divinity manifests through a spectrum of energies and conscious play. Through comparative analysis of classical texts and modern scholarly interpretations, the paper elucidates the nuanced dialogues between static monism and dynamic realism. It further investigates the implications of these doctrines for contemporary spiritual practice and philosophical inquiry. Methodology: In this paper, the exploratory qualitative research method is used. The relevant information is collected using keyword-based search in Google search engine, Google Scholar search engine, and AI-driven GPTs. This information is analysed and interpreted as per the objectives of the paper. Results/ Analysis: Ultimately, the synthesis of Advaita Vedanta and Kashmir Shaivism enriches the global discourse on spirituality and metaphysics, offering profound lessons on unity, transformation, and the quest for truth in an ever-evolving world. This inquiry reaffirms the timeless appeal of non-dualistic perspectives while challenging modern intellectual paradigms by merging analytical rigor with mystical insight. Originality/ Values: This research contributes to a deeper understanding of non-dualistic thought and its transformative potential in bridging ancient wisdom with modern existential challenges. Ultimately, these insights illuminate deep paths to inner peace and clarity.